Dyrektorzy szkół w Polsce – wymagania, struktura, zadania - Madalińska-Michalak, Joanna (Studia Edukacyjne, 2019)
The paper presents the findings derived from the study on school principals in Poland. The study is guided by the following research questions: What requirements are addressed to candidates for the position of a school principal? Who are school principals? How does the structure of school principals look like? What tasks does the school principal have to perform? The basis of the research study is the review of the laws in force from September 1, 2018 in the field of education and accompanying executive regulations, as well as the analysis of data available in the database of the Educational Information System and the data of the Ministry of National Education. The findings inform about educational policy and practice and at the same time contribute to further research on the socio-professional status of school principals in Poland as well as on research on working conditions and the professionalization of school principal activities.